Skeletal effects of the estrogen and calcitonin in ovarectoized rats - Kavuncu, V; Sahin, S; Baydas, G; Ilhan, N; Ozercan, I; Yasar, A; Ozercan, R (Springer-Verlag London Ltd, 2000)
[Abstract Not Available]